High proportion of patients with bleeding of unknown cause in persons with a mild‐to‐moderate bleeding tendency: Results from the Vienna Bleeding Biobank (VIBB). Issue 3 (1st February 2018) - Gebhart, J.; Hofer, S.; Panzer, S.; Quehenberger, P.; Sunder‐Plassmann, R.; Hoermann, G.; Eigenbauer, E.; Haslacher, H.; Kepa, S.; Kyrle, P. A.; Eichinger, S.; Knöbl, P.; et al.
Abstract : Introduction: Data on clinical characteristics and the prevalence of underlying coagulopathies in patients with mild‐to‐moderate bleeding disorders (MBDs) are scarce. Aim: We established the Vienna Bleeding Biobank (VIBB) to characterize and thoroughly investigate Austrian patients with MBDs. Results: Four hundred eighteen patients (female = 345, 82.5%) were included. A platelet function defect (PFD) was diagnosed in 26 (6.2%) and a possible PFD in 30 (7.2%) patients. Eight patients (1.9%) were diagnosed with von Willebrand disease (VWD) (type 1 n = 6; type 2 n = 2), and 29 patients had low VWF (30‐50 IU/dL). Deficiencies in factor VIII, IX, XI or XIII were found in 11 (2.6%), 3 (0.7%), 3 (0.7%) and 1 patient(s), 2 patients had dysfibrinogenaemia, and further 2 had possible PFD and FXI deficiency. Probable causal mutations were detected in 8 of 11 patients with FVIII deficiency, 2 of 3 patients with FIX deficiency and 2 of 8 patients with VWD. Three hundred three patients (72.5%) had normal results in the coagulation assays and were categorized as patients with bleeding of unknown cause (BUC). The bleeding score did not differ between patients with and without established diagnosis. A diagnosis of a bleeding disorder was more frequently made in men than in women (49.3% vs 22.9%). Male sex (OR 3.55, 95% CI: 2.02‐6.22; P < .001) and blood group 0 (OR 1.86, 95% CI: 1.17‐2.94; P = .008) were independently associated with diagnosis of a bleeding disorder. Conclusion: The high rate of patients with BUC despite in‐depth haemostatic assessment underlines the incompleteness of available routine laboratory tests. Males with MBDs were more likely to be diagnosed with an established bleeding disorder than females.